Analisis Efisiensi dan Efektivitas Pengelolaan Anggaran Pada Kementerian Lingkungan Hidup dan Kehutanan Tahun 2020–2024 - Stevani, Aurel; Muchammad Saifuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Public budget management in the environmental and forestry sectors is a crucial component in supporting sustainable development and good governance. This study aims to analyze the efficiency and effectiveness of budget management at the Ministry of Environment and Forestry (KLHK) of Indonesia for the 2020–2024 period, focusing on spending efficiency indicators and the effectiveness of non-tax state revenue (PNBP). The research employs a descriptive quantitative analysis based on secondary data from KLHK’s financial reports, state budget (APBN) documents, and official government publications. The efficiency ratio is calculated as the percentage of expenditure realization against the allocated budget, while the effectiveness of PNBP is measured as the percentage of realization against the target. The findings show that KLHK’s spending efficiency ranged from 86.51% to 98.36%, indicating sound budget control without excessive expenditure. Meanwhile, PNBP effectiveness consistently exceeded targets, with the highest achievement of 121.27% in 2021 and the lowest of 103.19% in 2023. Overall, KLHK’s budget management is assessed as both efficient and effective, supporting the achievement of strategic programs in the environmental and forestry sectors. These findings provide valuable insights for improving public fiscal policy, particularly in the context of transparency and accountability.